Answer: The required function formula is,
D(t) = 160 - 25 t
Step-by-step explanation:
Given,
The total distance of her from the safe zone = 160 meters,
And, after 3 seconds she is 85 meters far away from the safe zone,
Thus, the total distance she covered in 3 seconds = 160 - 85 = 75 meters,
Since, she drove at a constant speed,
Also,
Thus, the distance she will cover in t seconds = 25 t
( Because, Distance = Speed × Time )
Hence, the total distance of her from the safe zone after t seconds, D(t) = 160 - 25t
Which is the required function formula.
Kayden drives at a constant speed. The function D(t) can be represented as .
Given information:
Kayden is a stunt driver.
Total distance of safe zone is 160 m.
She drove with a constant speed.
After 3 seconds of driving, she was 85 meters away from the safe zone.
So, the distance traveled in 3 seconds will be 160-85=75 m.
Now, the speed of the driver will be,
The distance traveled in t seconds will be 25t.
So, the equation representing the given condition will be,
Therefore, the function D(t) can be represented as .
For more details, refer to the link:
Answer:
length of book mark =9cm
breadth of bookmark=2cm
area of bookmark=length×breadth
=9cm×2cm
=18cm answer
The area of the bookmark is found by multiplying its length (9 cm) by its width (2 cm), giving a total of 18 square centimeters.
The area of a shape is calculated by multiplying the length by the width. In this case, the length of the bookmark is 9 centimeters and the width is 2 centimeters. So, the area of the bookmark will be 9 cm multiplied by 2 cm which equals to 18 square centimeters.
#SPJ2
5x-3y=6 and 2x-5y=10
The solution to the system of equations 5x-3y=6 and 2x-5y=10 is x = 0 and y = -2.
To find the solution to the system of equations:
5x - 3y = 6 ...(1)
2x - 5y = 10....(2)
Use the elimination method to find the solution:
Multiply both sides of equation (1) by 2 to make the coefficients of 'x' in both equations equal:
2(5x - 3y) = 2(6)
10x - 6y = 12
Now, we have the following two equations:
10x - 6y = 12
2x - 5y = 10
Multiply both sides of equation (2) by 5 to make the coefficients of 'y' in both equations equal:
5(2x - 5y) = 5(10)
10x - 25y = 50
Now, we have the following two equations:
10x - 6y = 12...(3)
10x - 25y = 50...(4)
Subtract equation (3) from equation (4) to eliminate 'x':
(10x - 25y) - (10x - 6y) = 50 - 12
-19y = 38
Divide both sides by -19 to solve for 'y':
y = 38 / -19
y = -2
Now that we have the value of 'y', substitute it back into either equation (1) or (2) to find 'x'.
Use equation (1):
10x - 6(-2) = 12
10x + 12 = 12
Subtract 12 from both sides:
10x = 0
x = 0
So, the solution to the system of equations is x = 0 and y = -2.
To learn more on Equation:
#SPJ6